Discriminating between extinct and extant life detection: implications for future Mars missions - Dzurilla, Katherine A.; Teece, Bronwyn L. (Frontiers in Astronomy and Space Sciences, 2024)
The search for biosignatures on Mars has been a high priority for astrobiology. The approach to detecting putative biosignatures has largely been focused on chemical analyses targeting predominantly extinct life. However, this approach has limited the characterization of extant life, preventing differentiation between extinct and extant biosignatures. Detecting an extant martian lifeform requires approaches focused on identification of biological features. Identifying potential features of life, such as growth or reproduction, can contribute evidence necessary to identify extant biosignatures. While an unambiguous extant biosignature might not be possible with biologically focused approaches, the combined data can provide supporting evidence to attribute a biosignature to an extinct or extant lifeform in conjunction with flight tested instrumentation. With upcoming initiatives, such as the planned Mars Sample Return campaign and the Mars Life Explorer mission concept, the incorporation of extant life specific analysis is paramount for the future of Mars exploration.